Returning Samples From Enceladus for Life Detection - Neveu, Marc; Anbar, Ariel D.; Davila, Alfonso F.; Glavin, Daniel P.; MacKenzie, Shannon M.; Phillips-Lander, Charity M.; Sherwood, Brent; Takano, Yoshinori; Williams, Peter; Yano, Hajime (Frontiers in Astronomy and Space Sciences, 2020)
Evidence suggests that Saturn’s icy moon Enceladus has a subsurface ocean that sources plumes of water vapor and ice vented to space from its south pole. In situ analyses of this material by the Cassini spacecraft have shown that the ocean contains key ingredients for life (elements H, C, N, O and possibly S; simple and complex organic compounds; chemical disequilibria at water-rock interfaces; clement temperature, pressure, and pH). The Cassini discoveries make Enceladus’ interior a prime locale for life detection beyond Earth. Scant material exchange with the inner Solar System makes it likely that such life would have emerged independently of life on Earth. Thus, its discovery would illuminate life’s universal characteristics. The alternative result of an upper bound on a detectable biosphere in an otherwise habitable environment would likewise considerably advance our understanding of the prevalence of life beyond Earth. Here we outline the rationale for returning vented ocean samples, accessible from Enceladus’ surface or low altitudes, to Earth for life detection. Returning samples allows analyses using laboratory instruments that cannot be flown, with decades or more to adapt and repeat analyses. We describe an example set of measurements to estimate the amount of sample to be returned and discuss possible mission architectures and collection approaches. We then turn to the challenges of preserving sample integrity and implementing planetary protection policy. We conclude by placing such a mission in the broader context of Solar System exploration.